Emerging trends in religious liberty during the 2000-2001 term of the United States Supreme Court - Destro, Robert A. (2001)
Abstract der Zeitschrift: From a religious liberty perspective, the October 2000 Term of the United States Supreme Court was relatively uneventful. The Court decided only one case raising significant religious liberty concerns, Good News Club v. Milford Central School. Good News Club case adds little to the First Amendment case law already on the books, but it does provide an excellent opportunity to highlight the growing need for well-informed scholars, both American and foreign, to examine the relationships between and among the clauses of the First and Fourteenth Amendments tothe Constitution of the United States
Keywords: Staatskirchenrecht; Religionsfreiheit; Glaubensfreiheit; Rechtsprechung; Amerika; Usa